A study of neuroinflammation in a mouse model of Alzheimer's disease - Gallagher, Joseph J. (Trinity College (Dublin, Ireland). Department of Physiology, 2010)
Microglia are the principal immune-competent cell of the central nervous system (CNS) and there is evidence to suggest microglia are the co-ordinating cells of the CNS inflammatory response. The blood brain barrier (BBB) isolates the CNS from the rest of the body and limits the delivery of therapeutic agents to the CNS. Nanotechnology-based CNS drug delivery techniques, designed to bypass the restrictive nature of the BBB, often involve several constituents to mediate passage across the BBB. Little is known about the microglial response to such materials. A polyelectrolye coated magnetic fluorescent nanostructure was evaluated in this study. The nanostructure exhibited no cytotoxic effects, internalization of the nanostructure did not induce a robust microglial activation and no meaningful increase in cytokine production was observed, although phagocytosis did occur.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin